MENIKAHI WANITA HAMIL KARENA ZINA DALAM PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN - ASMANIZAR ASMANIZAR (PREMISE LAW JURNAL, 2016)
This article analyzes the regulation on adultery, status and legal consequences of marrying pregnant woman because of adultery from the perspective of the Islamic law and Law No 1/1974 on Marriage. The research used judicial normative and descriptive analytic method. The regulation on adultery is stipulated in the Islamic law. Meanwhile, Law on Marriage only regulates the status of a child from adultery in civil law with his mother and with his mother’s relatives. Legal status in the Islamic law of a marriage with pregnant a woman because of adultery is valid for the man who has made her pregnant, while there is different opinion about the validity of marriage of a man who does not make her pregnant. According to the Marriage Law, a marriage with a pregnant woman is valid when it is done according to the couple’s religion. The legal consequence of marrying in this case regarding to the child in relationship in kinship, guardianship, inheritance, and livelihood with his parents or the man who has married his mother since the pregnant woman is married legitimately. Keywords: Marriage, Adultery, Pregnant Woman Because of Adultery